Person-centered expressive arts therapy - Rogers, Natalie (Psychological Counseling and Psychotherapy, 1970)
Expressive arts therapy uses the expressive arts – movement, art, music, writing, sound, and improvisation — in a supportive setting to facilitate growth and healing. It is a process of discovering ourselves through any art form that comes from an emotional depth.